Growth Performance of Broilers in Response to Increasing Concentration of Multiple Mycotoxins in Contaminated Corn - Allison K. Blomme; Khairy I. Jenkins; Kara M. Dunmire; Nelsa M. Beckman; Haley K. Otott; Charles R. Stark; Chad B. Paulk (Kansas Agricultural Experiment Station Research Reports, 2022)
Mycotoxins in grains are a result of mold or fungal growth from environmental stressors and cause detrimental impacts to poultry production. Thus, the objective of this experiment was to determine the effects of increasing concentration of a combination of mycotoxins on growth performance of broiler chicks. A total of 250 one-day-old male broilers (Cobb 500; initial BW 0.092 lb) were used in a 15-d study. Broilers were housed in 3 Petersime batteries withad libitumaccess to feed and water. Treatments were randomly assigned to 1 of 50 cages within location block, resulting in 10 cages per treatment with 5 broilers per cage balanced by BW. For this experiment, the sourced contaminated corn contained 8.2 ppm fumonisin (FUM), 8.0 ppm deoxynivalenol (DON), and 551 ppb zearalenone (ZEA). Dietary treatments consisted of 0%, 25%, 50%, 75%, and 100% of the mycotoxin contaminated corn replacing non-contaminated corn. The resulting complete diet mycotoxin concentrations were 1.5 ppm, 1.4 ppm, 2.3 ppm, 2.9 ppm, and 3.9 ppm for FUM;<0.6 ppm, 1.0 ppm, 1.4 ppm, 2.3 ppm, and 3.0 ppm for DON; and<51.7 ppb, 94.5 ppb, 180.5 ppm, 294.6 ppb, and 364.1 ppb for ZEA, respectively. Data were analyzed as a completely randomized design with cage as the experimental unit using the GLIMMIX procedure of SAS 9.4 (Cary, NC). Results were considered significant atP≤ 0.05. Total body weight gain (BWG) decreased (linear,P= 0.007) and feed intake (FI) tended to decrease (linear,P= 0.093) in broilers fed diets with increasing concentration of mycotoxin contaminated corn in the diet. The increase in mycotoxin concentration in diets fed to broilers also resulted in poorer (linear,P= 0.010) feed conversion ratio (FCR). In conclusion, increasing concentrations of FUM, DON, and ZEA in broiler feed negatively impacted BWG, FI, and FCR even when the mycotoxin levels were below acceptable limits for individual mycotoxins.
Keywords: broiler growth; broiler nutrition; mycotoxins; mycotoxin contamination